A rare case of zolendronate infusion complication leading to glaucoma filtration surgery - Khan A (Dove Medical Press, 2011)
A Khan1, G Lascaratos1, T Rane-Malcolm2, R Sanders21Princess Alexandra Eye Pavilion, Edinburgh, 2Department of Ophthalmology, Queen Margaret Hospital, Dunfermline, Fife, UKAbstract: Zolendronic acid is a nitrogenous biphosphonate commonly used as an intravenous infusion for the management of Paget’s disease, osteoporosis, and hypercalcemia of malignancy. We report a rare and challenging complication of zolendronate infusion: unilateral acute anterior uveitis followed by persistently raised intraocular pressure despite being on four different classes of antiglaucoma medication. The challenge was that the patient required topical steroid to treat her uveitis in the background of known glaucoma with corresponding steroid response. She eventually underwent a left phacotrabeculectomy augmented with 5-fluorouracil. Four weeks postoperatively she developed an encapsulated bleb and underwent needling with 5-fluorouracil. This case highlights the importance of having a high index of suspicion for anterior uveitis in patients with a red and painful eye after initiating biphosphonate therapy. Caution should also be exercised when prescribing biphosponates to glaucoma patients.Keywords: biphosponates, anterior uveitis, intraocular pressure